Association of sex‐specific donor skeletal muscle index with surgical outcomes in living donor liver transplantation recipients. (21st November 2022) - Sim, Ji‐Hoon; Kim, Kyung‐Won; Ko, YouSun; Kwon, Hye‐Mee; Moon, Young‐Jin; Jun, In‐Gu; Kim, Sung‐Hoon; Kim, Seonok; Song, Jun‐Gol; Hwang, Gyu‐Sam
Abstract: Background: A recent study reported a correlation between the muscle mass of male donors and graft failure in living donor liver transplantation (LDLT) recipients. We investigated the association of sex‐specific donor skeletal muscle index (SMI) with mortality and graft failure in LDLT recipients. Methods: We retrospectively analysed 2750 sets of donors and recipients between January 2008 and January 2018. The recipient outcomes were analysed by dividing the data according to donor sex. Cox regression analyses were performed to evaluate the association between donor SMI by sex and 1‐year mortality and graft failure in recipients. Results: In the male donor group, robust donor (increased SMI) was significantly associated with higher risks for mortality (hazard ratio [HR]: 1.03, 95% confidence interval [CI]: 1.00–1.06, p = .023) and graft failure (HR: 1.04, 95% CI: 1.01–1.06, p = .007) at 1 year. In the female donor group, the robust donor was significantly associated with lower risks for mortality (HR: 0.92, 95% CI: 0.87–0.97, p = .003) and graft failure (HR: 0.95, 95% CI: 0.90–1.00, p = .032) at 1 year. Conclusions: Donor SMI was associated with surgical outcomes in recipients. Robust male and female donors were a significant negative and protective factor for grafts respectively.